Popular Culture as an Inspiration for New Professions - Kust, Izabella (Kultura-Społeczeństwo-Edukacja, 2019)
Popular culture constitutes an inseparable part of social life. New forms and means of cultural expression continuously come into existence. Social, economic, and cultural changes influence popular culture, which in turn affects attitudes and behaviours of various social groups in a variety of manners. The phenomenon of popular culture is also discussed from the perspective of educational processes. The learning process involves shaping attitudes towards reception of culture and the need for life-long learning. Polysemic nature of popular culture inspires various activities and actions, including the emergence of new jobs, such as a fashion technician, leisure market researcher, or video filmmaker. Among the jobs of the future, the following new ones are listed: a manager in multicultural context, theme park animator, and social marketing specialist. According to the prognosis for the job market, a job of the future is the job which enables great opportunities of employment and professional career. Popular culture generates new professions. Popular culture is an area, where (…) intergenerational or intercultural encounters may take place. A pedagogue learns from the young people about the things that are of importance and value to them (…). What should be emphasised here is the task of self-creation which is a difficult, regardless of age.